GPU-based Local Tone Mapping in the Context of Virtual Night Driving - Berssenbrügge, Jan; Bonner, Erik (Proceedings of the ASME 2012 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)

Self-Assessment for Evaluation and Improving the Product Development Processes in SMEs - Bensiek, Tobias; Kühn, Arno; Gausemeier, Jürgen; Grafe, Michael (Proceedings of the ASME 2012 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference, IDETC/CIE 2012, Chicago, IL, USA, August 12 – 15)

Model-Based Design of Mechatronic Systems by Means of Semantic Web Ontologies and Reusable Solution Element - Oestersötebier, Felix; Just, Viktor; Trächtler, Ansgar; Bauer, Frank; Dziwok, Stefan (Proceedings of the ASME 2012 11th Biennial Conference on Engineering Systems Design and Analysis)
When designing complex mechatronic systems, a team of developers will be facing many challenges that can impede progress and innovation if not tackled properly. In meeting them simulation tools play a central role. Yet it is often impossible for a single developer to foresee the overall impact a design decision will have on the system and on the other domains involved. For this task multi-domain simulation tools exists, but because of its complexity and the different levels of detail that are needed, the effort to specify a complete system from scratch is very high. Another challenge is the selection of the most suitable solution elements provided by the manufacturers. Currently they are often chosen manually from catalogues. The development engineer is therefore usually inclined to employ well-known solution elements and suppliers. To tackle both challenges our aim is an increase in efficiency and innovation by means of generally available solution knowledge, such as well-proven solution patterns, ready-to-use solution elements, and established simulation models [1]. Our paper presents a tool-supported, sequential design process. From the outset, the comprehensive functional capability of the designed system is supervised by means of multi-domain simulation. At significant points in the design process, solution knowledge can be accessed as it is stored in ontologies and therefore available via Semantic Web [2]. Thus, one can overcome barriers resulting from different terminologies or referential systems and furthermore infer further knowledge from the stored knowledge. The paper focuses on an early testing in the conceptual design stage and on the subsequent semantic search for suitable solution elements. After the specification of a principle solution for the mechatronic system by combining solution patterns, an initial multi-domain model of the system is created. This is done on the basis of the active structure and of idealized simulation models which are part of a free library and associated with the chosen solution patterns via the ontologies. In further designing the controlled system and its parameters with the completed model, the developer defines additional criteria to be fed into the subsequent semantic search for solution elements. Information on the latter is provided by the manufacturers as well as detailed simulation models, which are used to analyze the functional capability of the concretized system. Therefore, the corresponding idealized models are replaced automatically with the parameterized models of the solution elements containing for example the specific friction model for the chosen motor. We show this process using the concrete example of a dough-production system. In particular, we focus on its transport system. Resulting requirements for the simulation models and their level of detail are expound, as well as the architecture and benefits of the ontologies. [1] Bauer, F., Anacker, H., Gaukstern, T., Gausemeier, J., Just, V., (2011), “Analyzing the dynamic behavior of mechatronic systems within the conceptual design”, Proceedings of the 18th International Conference on Engineering Design (ICED11), 4, Copenhagen, pp. 329-336. [2] Berners-Lee, T., Hendler, J.; Lassila, O., (2001), “The Semantic Web”, Scientific American, 284(5), pp. 34–43.

Computer support for the identification of solution patterns for the conceptual design of advanced mechatronic systems - Dumitrescu, Roman; Anacker, Harald; Bauer, Frank; Gausemeier, Jürgen (Proceedings of the ASME 2012 11th Biennial Conference on Engineering Systems Design and Analysis)

Development of Product Piracy Robust Products and Production Systems - Kokoschka, Martin; Gausemeier, Jürgen; Lehner, Markus (Proceedings of 18th International ICE-Conference on Engineering, Technology and Innovation)

Development of Product Piracy Robust Products and Production Systems

Stakeholder based innovation management - Gausemeier, Jürgen; Lehner, Markus; Peitz, Christoph; Grote, Anne-Christin

Knowledge-based Zooming Technique for the Interactive Analysis of Mechatronic Systems - Radkowski, Rafael; Wassmann, Helene (IEEE International Conference on Intelligent Engineering Systems (INES) 2012)

Pattern-Based Integrative Design of Molded Interconnect Devices (MID) - Dumitrescu, Roman; Gaukstern, Tobias; Jürgenhake, Christoph; Gausemeier, Jürgen; Kühn, Arno

Maturity Based Improvement of Product Development Processes in Small and Medium-Sized Enterprises - Bensiek, Tobias; Kühn, Arno; Gausemeier, Jürgen; Grafe, Michael (Proceedings of the 12th International Design Conference)

The production of tomorrow - additive manufacturing processes in industrial use - Klemp, Eric; Wall, Marina (Digital Engineering Magazin)

Developing products and production systems integratively - modeling and analysis in the early days Phase of product creation

Thinking ahead the Future of Additive Manufacturing Scenario-based Matching of Technology Push and Market Pull - Gausemeier, Jürgen; Echterhoff, Niklas; Kokoschka, Martin; Wall, Marina (Fraunhofer Direct Digital Manufacturing Conference 2012)

Stakeholder analysis in developing technology strategies - Gausemeier, Jürgen; Lehner, Markus; Peitz, Christoph

Model-based design of two cooperating Delta Robot - Teichrieb, Heinrich; Just, Viktor; Dziwok, Stefan; Pohlmann, Uwe; Schierbaum, Thomas; Tr {\ "a} chtler, Ansgar

Kooperationsbedingte Identitäts- und Kompetenzentwicklung von Grundschullehrkräften - Bloh, Thiemo

Optimierung des einsatzbezogenen Lernens durch Wissensidentifikation - Pottebaum, Jens
Keywords: Arbeitsorganisation; E-Learning; Lernorganisation; Lerntechnik; Wissensmanagement

IT-Unterstützung für Public Safety & Security: Interdisziplinäre Anforderungsanalyse, Architekturen und Gestaltungskonzepte (IT4PSS 2012) - König-Ries, Birgitta; Pipek, Volkmar; Pottebaum, Jens; Strohschneider, Stefan (Software Engineering 2012: Fachtagung des GI-Fachbereichs Softwaretechnik, 27. Februar - 2. März 2012 in Berlin)
Keywords: Ver{\

245 GHz subharmonic receiver in SiGe - Mao, Yanfei; Scheytt, Christoph; Schmalz, Klaus; Borngräber, Johannes (Microwave Integrated Circuits Conference (EuMIC), 2012 7th European)
A subharmonic receiver for sensing applications in the 245 GHz ISM band has been proposed. The receiver consists of a single-ended common base LNA, a 60 GHz push-push VCO with 1/32 divider, a transconductance 4th subharmonic mixer and IF amplifier. The receiver is fabricated in fT/fmax=300/500 GHz SiGe: C BiCMOS technology. Its measured single-ended gain is 21 dB at 243 GHz with tuning range of 12 GHz, and the single- side band noise figure is 32 dB. The input 1-dB compression point is at -37 dBm. The receiver dissipates a power of 358 mW.

120 GHz Radar Mixed-Signal Transceiver - Debski, Wojciech; Winkler, Wolfgang; Sun, Yaoming; Marinkovic, Miroslav; Borngräber, Johannes; Scheytt, Christoph (Microwave Integrated Circuits Conference (EuMIC), 2012 7th European)
The design of a complex integrated transceiver for 121–124 GHz is presented. The transceiver consists of the transmitter with VCO, power amplifier and power detectors, the receiver with LNA, two mixers for quadrature receive path and variable gain amplifiers for IF-output and the digital control circuits with SPI-interface. A central part is the VCO with DAC and memory for on-chip storage of programmable frequency ramps for FMCW radar applications. The oscillator phase noise is -92 dBc/Hz at 1MHz offset. For calibration of the radar-system on chip, a frequency measurement unit is integrated. The radar chip has power consumption of 380 mW and occupies an area of 1.8 mm x 1.5 mm. Several examples of frequency ramp generation are presented. The chip is intended for integration together with antenna in a single package.

Microwave Biosensor for Characterization of Compartments in Teflon Cappilaries - Wessel, Jan; Schmalz, Klaus; Cahill, Brian; Gastrock, Gunter; Scheytt, Christoph (Microwave Conference (EuMC), 2012 42nd European)
A passive microwave sensor based on microstrip lines for characterizing cell cultivation in aqueous compartments is presented. The proposed design methodology leads to a highly sensitive biosensor structure, which is fabricated on Rogers 3003 material. It is shown that a sufficiently high sensitivity is achieved to monitor the cultivation stadium of a yeast culture based on detection of permittivity changes. The obtained measurement results show good agreement with the performed full 3D EM simulations. According to these results the presented biosensor is capable of characterizing the stage of yeast cultivation label-free and contactless.

Scalable and Flexible Vision-Based Multi-Robot Tracking System - Tanoto, Andry; Li, Hanyi; Rückert, Ulrich; Sitte, Joaquin (In Proceedings of the IEEE International Symposium on Intelligent Control (ISIC))
Precise position is necessary for a robot to reliably localize itself and navigate in the environment. Robot position can be calculated internally or acquired from an external system. This paper presents a software architecture of a vision-based robot tracking system that can provide precise position information as well as identification of many robots. The software architecture has been designed to take into consideration the need for a flexible and scalable system that can interoperate with many similar systems and support different types of image sources, image processing, and outputs. With the architecture, future enhancements or replacements can be implemented as plug-ins, which can be easily integrated into the system. This paper also demonstrates the proposed architecture in different application scenarios

Performance Estimation of Fully Digital Polar Modulation driving a 2 GHz Switch-Mode Power Amplifier - Ostrovskyy, Philip; Heuermann, Holger; Sadeghfam, Arash; Scheytt, Christoph (Microwave Integrated Circuits Conference (EuMIC), 2012 7th European)
Abstract— This paper presents a fully digital transmitter architecture based on a digital polar modulator (DPM) and switch-mode power amplifier (SMPA). A simple method for comparison and estimation of different digital modulation techniques for SMPA is described. An estimation of the proposed digital polar modulator properties was done by means of a 2.1..2.2 GHz class-F power amplifier. For a CDMA signal with 9.5 dB peak-to-average power ratio (PAPR), the class-F based amplifier module driven by DPM pulse train shows more than 1 W output power and more than 10 % of drain efficiency.

245-GHz subharmonic receiver in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (Microwave Theory and Techniques, IEEE Transactions on)
A subharmonic receiver for sensing applications in the 245 GHz ISM band has been proposed. The receiver consists of a single-ended common base LNA, a 60 GHz push-push VCO with 1/32 divider, a transconductance 4th subharmonic mixer and IF amplifier. The receiver is fabricated in fT/fmax=300/500 GHz SiGe: C BiCMOS technology. Its measured single-ended gain is 21 dB at 243 GHz with tuning range of 12 GHz, and the single- side band noise figure is 32 dB. The input 1-dB compression point is at -37 dBm. The receiver dissipates a power of 358 mW. Index Terms— SiGe technology, millimeter-wave circuits, 245 GHz, CB LNA, SHM, VCO, sub-harmonic receiver.

A 5-Gb/s 2.1–2.2-GHz Bandpass Δ Σ Modulator for Switch-Mode Power Amplifier - Ostrovskyy, Philip; Gustat, Hans; Ortmanns, Maurits; Scheytt, Christoph (Microwave Theory and Techniques, IEEE Transactions on)
A tunable fourth-order bandpass ΔΣ modulator (BDSM) designed and fabricated in 0.25μm SiGe BiCMOS technology is presented. The designed modulator relaxes switching conditions for the amplification stage of the switch-mode power amplifier in comparison to the BDSM architecture. The BDSM is clocked at 5 GHz, while the notch frequency can be tuned in a range of 2.1-2.2 GHz. The modulator achieves 46.6-dB signal-to-noise and distortion ratio in 10-MHz bandwidth for a sine-wave input at 2.2 GHz consuming 330 mW from a 3-V supply. The BDSM was also tested with a single-channel WCDMA signal. It has demonstrated 42.2-dBc adjacent channel leakage ratio at 5-MHz offset and less than 2.1% error vector magnitude over the tuning range.

A Compact Linear 60-GHz PA With 29.2% PAE Operating at Weak Avalanche - Sun, Yaoming; Fischer, Gerhard G.; Scheytt, Christoph (Microwave Theory and Techniques, IEEE Transactions on)
This paper presents a 60-GHz SiGe PA with a 29.2% power-added efficiency (PAE), a peak power of 16.8 dBm, and a peak output 1-dB compression (OP 1dB ) of 14 dBm. Its measured gain is 13.5 dB at 60 GHz with a corresponding 3-dB bandwidth of 47-74 GHz. The PAE is above 25% with a supply voltage from 2.2 to 4 V. A cascode stage has been analyzed and used as the amplifier core. The high PAE is achieved by pushing the upper transistor of the cascode stage to weak avalanche area and correct transistor sizing. The linearity is achieved by optimizing the input matching and emitter degeneration. Safe operation conditions of heterojunction bipolar transistors at dc and high frequencies have been investigated at weak avalanche area. A safe operation boundary for high frequencies is given based on our experimental results and analytical derivations. Large-signal stress tests have shown there is no performance degradation and have proved the validity of this safe operation boundary.

Low-Power SiGe BiCMOS Transimpedance Amplifier for 25-GBaud Optical Links - Sedighi, Behnam; Scheytt, Christoph ((Refa) FB/IE Zeitschrift für Unternehmensentwicklung und Industrial Engineering)
We propose a new circuit for the realization of transimpedance amplifiers (TIAs), targeted at reducing the input-referred noise of the TIA or alternatively increasing the bandwidth, without increasing the power dissipation. An intensive theoretical analysis of the method is given. A prototype chip is fabricated in 0.25- μm SiGe BiCMOS technology. The TIA has a gain of 71 dBΩ , a bandwidth of 20.5 GHz, and an average input-referred current noise density of 18 pA/√Hz . The circuit operates from a 2.5-V supply, and power dissipation is 57 mW.

SiGe BiCMOS Transceivers, Antennas, and Ultra-Low-Cost Packaging for the ISM Bands at 122 and 245 GHz - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Wang, Ruoyu (IMS 2012 (International Microwave Symposium))
This paper reviews recent results of wireless transmitter and receiver ICs at 122 and 245 GHz in 0.13 µm SiGe BiCMOS technology together with an efficient on-chip antenna. A transmitter IC with 5 dBm output power and directional onchip power measurement for built-in-self-test is presented. A 122 GHz passive HBT diode mixer design is discussed and results are shown. The mixer exhibits superior 1/f noise performance which makes it especially suitable for FMCW/CW radar sensors. Furthermore a highly integrated 245 GHz transmitter with 1 dBm maximum output power was realized. The IC dissipates only 380 mW. A low-loss on-chip antenna for 130 GHz with 60% efficiency was implemented and measured. It uses localized backside etching techniques and allows for simplified and very cost-efficient mm-wave packaging

A 245 GHz transmitter in SiGe technology - Schmalz, Klaus; Borngräber, Johannes; Heinemann, Bernd; Rücker, Holger; Scheytt, Christoph (Radio Frequency Integrated Circuits Symposium (RFIC), 2012 IEEE)
A 245 GHz transmitter for sensing applications has been realized, which consists of a push-push VCO with 1/64 frequency divider, a transformer- coupled one-stage power amplifier, and a frequency doubler. It is fabricated in 0.13μm SiGe:C BiCMOS technology with f T /f max of 300GHz/500GHz. The peak output power of the transmitter is 2 dBm. The 3-dB bandwidth reaches from 229 GHz to 251 GHz. The output power is 1 dBm at 245 GHz. The transmitter dissipates 0.29 W. Additionally, a test-circuit with an integrated two-stage power amplifier and a frequency doubler is presented, which reaches 1.4 dBm at 245 GHz and dissipates 0.19 W.

An integrated 125GHz Sensor with read-out circuit for permittivity measurement of liquids - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
In this publication an integrated dielectric sensor with read-out circuit in SiGe BiCMOS technology at 125GHz is presented. The sensor consist of a 500 µm shorted half-wave coplanar waveguide transmission line in the top metal layer. Read-out of the sensor is performed by measurement of its reflection coefficient with an integrated multiprobe reflectometer and signal source. The MMIC has been fabricated in a 190-GHz f T SiGe:C BiCMOS technology and assembled on a printed circuit board. Functionality of the sensor is demonstrated with a stimulus frequency from 118 to 133GHz with immersion of the sensor into a binary methanol-ethanol mixture.

A fully digital polar modulator for switch mode RF power amplifier - Ostrovskyy, Philip; Scheytt, Christoph; Lee, SungJun; Park, BongHyuk; Jung, JaeHo (Proc. IEEE Int Circuits and Systems (ISCAS) Symp)
In this paper, a novel fully digital modulator for a switch mode power amplifier (SMPA) is presented. The modulator converts the input baseband amplitude and phase signals into a two-level pulse train for driving an RF SMPA. The simulation results demonstrated a proof of the concept. The proposed architecture is analyzed in terms of accuracy by measuring EVM. The impact of the modulator parameters on the SMPA performance is investigated and corresponding results are shown. The modulator was simulated with a 20 MHz LTE signal.

Vertical Graphene Base Transistor - Mehr, Wolfgang; Dabrowski, Jarek; Lemme, Max C.; Lippert, Gunther; Lupina, Grzegorz; Ostling, Mikael; Xie, Ya-Hong; Scheytt, Christoph ((Refa) FB/IE Zeitschrift für Unternehmensentwicklung und Industrial Engineering)
We present a novel graphene-based-device concept for a high-frequency operation: a hot-electron graphene base transistor (GBT). Simulations show that GBTs have high current on/off ratios and high current gain. Simulations and small-signal models indicate that it potentially allows terahertz operation. Based on energy-band considerations, we propose a specific material solution that is compatible with SiGe process lines.

60 GHz Polarimetric MIMO Sensing: architectures and technology - Garcia-Ariza, Alexis-Paolo; Müller, Robert; Stephan, Ralf; Wollenschläger, Frank; Schulz, Alexander; Elkhouly, Mohamed; Scheytt, Christoph; Trautwein, Uwe; Müller, Jens; Thomae, Reiner; Hein, Matthias (EuCAP2012 (European Conference on Antennas and Propagation))
Millimeter-Wave (mm-W) is considered a potential technology for high-data rate wireless transmission and for high-resolution short-range radar, due to the 7-9 GHz bandwidth at the 60 GHz unlicensed band available worldwide. Developing ultrawideband architectures including multiple-input-multiple-output (MIMO) antenna systems at mm-W offer many advantages including jointly optimized analogue and digital signal processing at carrier frequency and baseband. This allows for flexible antenna designs and reduced losses, as many passive structures can be avoided at both sides of the link. Besides, based on flexible polarimetric approaches, the polarimetric propagation of electromagnetic waves can be exploited. In this paper we present a 60 GHz polarimetric MIMO system architecture, which includes analogue miniaturized frontends designed and manufactured by multi-layer packaging technologies. Such architecture permitted the design of compact MIMO radar and multi-dimensional channel sounding. The MIMO approach allows not only polarimetric filtering and fully polarimetric/directional signal processing to increase the signal-to-clutter-plus-noise ratio of mm-W radar systems, but also the full characterization of wireless channels including multipath with orthogonal polarizations.

120 GHz phased-array circuits in 0.25 µm SiGe BiCMOS technology - Elkhouly, Mohamed; Glisic, Srdjan; Ellinger, Frank; Scheytt, Christoph (GeMIC 2012)
This paper describes the design of D-band phased-array circuits in 0.25 μm technology. The first part describes the design of the passive components which are used in the phased-array systems such as balun, Wilkinson divider and branch-line coupler. A millimeter-wave vector-modulator is designed to support both amplitude and phase control for beam-forming applications. In the second part the designed circuits are integrated together to form a two channel 110-130 GHz phased-array chip. Each channel exhibits 360° phase control with 15 dB of amplitude control range and gain of -10 dB. The entire chip draws 45 mA from 3.3 V supply. The millimeter-wave phase shifting and the low-power consumption makes it ideal for highly integrated scalable beam-forming systems for both imaging and communication.

A 200mV 32b Subthreshold Processor with Adaptive Supply Voltage Control - Luetkemeier, Sven; Jungeblut, Thorsten; Porrmann, Mario; Rückert, Ulrich (Proc. IEEE Int. Solid-State Circuits Conf. Digest of Technical Papers)
In recent years, subthreshold operation has become a research focus for digital systems with limited energy budget (e.g. mobile, battery-powered devices, radio frequency identification (RFID), wireless sensor networks, or biomedical applications). Subthreshold operation allows for such low power consumption by reducing the supply voltage of the circuit below the threshold voltage of the transistors. As dynamic power depends quadratically on supply voltage, and static power depends exponentially on supply voltage, considerable power savings are achieved. At the same time propagation delays increase due to reduced transistor currents. Effectively, energy consumption per cycle can typically be reduced by a factor of 10 using subthreshold operation.

A 245 GHz CB LNA and SHM mixer in SiGe technology - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
The paper presents a four stage 245 GHz LNA in an f t /f max =280/425 GHz SiGe technology and a 4 th sub harmonic 245 GHz transconductance mixer in an f t /f max =250/300 GHz SiGe technology. The LNA takes advantage of common base (CB) topology for each stage and has 12 dB gain at 245 GHz, while exhibiting a 3 dB bandwidth of 26 GHz. It has a supply voltage of 2V and power dissipation of 28 mW. The transconductance mixer has -7 dB conversion gain at 245 GHz with an LO power of 8 dBm at 61 GHz. The mixer draws 9.8 mA at 3V. Simulation results of the receiver comprising the CB LNA and SHM mixer are given.

A 62GHz Reflectometer for Biomedical Sensor Readout in SiGe BiCMOS Technology - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (SiRF 2012 (Silicon Monolithic Integrated Circuits in RF Systems))
In this publication an integrated reflectometer in SiGe BiCMOS technology for sensor readout at 62 GHz is presented. The circuit includes an oscillator, a six-port reflectometer, and a dummy sensor for verification purposes. The circuit has a bandwidth of 8GHz at a center frequency of 62 GHz. It operates at 3.75V supply voltage and consumes 282 mW. The measurement principle is demonstrated and the scattering parameters of the dummy sensor are compared to measurement of a breakout circuit with a commercially available vector network analyzer. The circuit has been fabricated in a 190-GHz SiGe:C BiCMOS technology and occupies an area of 0.9 mm 2 .

122 GHz Radartransceiver und Komponenten in 0.13ym SiGe BiCMOS - Scheytt, Christoph; Debski, Wojciech; Sun, Yaoming; Wang, Ruoyu; Winkler, Wolfgang

Local Navigation Strategies for Multi-Robot Exploration - Tanoto, Andry; Rückert, Ulrich (From Simulation to Experimentation with Mini-Robots)
This paper presents two local navigation strategies for multi-robot systems in performing exploration of unknown environments. The strategies are based on the frontier cell for mapping the environment and navigating in it. Additionally, two coordination strategies are used to solve possible conflicts among robots. Key criteria investigated are the efficiency and effectiveness represented by the completion time, traveled distance, the total steps, and the task distribution. The developed algorithms are tested in simulations as well as in experiments with Khepera III mini robots running on the Teleworkbench. To evaluate the robustness of the developed algorithms, tests are performed under different environmental configurations and varying numbers of robots. The results show the advantages of both proposed strategies in different situations such as environment types and starting positions.

Multi-Robot System Validation: From Simulation to Prototyping with Mini Robots in the Teleworkbench - Tanoto, Andry; Werner, Felix; Rückert, Ulrich; Sitte, Joaquin (Advances in Autonomous Mini Robots)
One challenging aspect in the development of multi-robot systems is their validation in a real environment. However, experiments with real robots are considerably tedious as experimenting is repetitive and consists of several steps: setup, execution, data logging, monitoring, and analysis. Moreover, experiments also require many resources especially in the case when involving many robots. This paper describes the role of the Teleworkbench as a platform for conducting experiments involving mini robots. The Teleworkbench offers functionality that can help users in validating their robot software from simulation to prototyping using mini robots. A traffic management system is used as a scenario for demonstrating the support of the Teleworkbench for validating multi-robot systems.

Mixed-Signal PSSS-Empfänger - Scheytt, Christoph
PSSS-Dekodierschaltung, dadurch gekennzeichnet, dass das analoge PSSS-Eingangssignal mit N Spreizsequenzen und N Verknüpfungselementen (z. B. Multiplizierer) verknüpft werden und die Ausgangssignale der N Verknüpfungselemente mit N analogen Integrierern auf integriert werden, dass die Integrierer jeweils zum Beginn der empfangenen Spreizsequenzen gleichzeitig mit dem Signal SYNC zurückgesetzt werden, dass der Integrator über die Dauer einer Code-Sequenz das Eingangssignal auf integriert, dass nach der Integration an den Ausgängen der Integratoren jeweils das dekodierte Datensignal anliegt, dass die Ausgangssignale der Integrierer mit N parallelen einem AD-Wandler digitalisiert werden.

mm-Wave SOC and SIP Design for 122 GHz Radar SSensor in the EU-FP7 Project SUCCESS - Sun, Yaoming; Beer, Stefan; Scheytt, Christoph; Wang, Ruoyu; Zwick, Thomas (RF-MST Cluster Workshop on MEMSWAVE 2012)

40 Gb/s VCSEL driver IC with a new output current and pre-emphasis adjustment method - Sedighi, Behnam; Scheytt, Christoph (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
Design of a 40 Gb/s VCSEL driver IC capable of providing up to 10mA current to common-cathode VCSELs is presented. Using low-power bandwidth enhancement techniques, a prototype IC is successfully developed in 180-GHz SiGe BiCMOS technology. Measured results show 34 GHz of bandwidth, open eye diagram with rise/fall time below 10 ps, and power dissipation of 130 mW.

Low-power BiCMOS track-and-hold circuit with reduced signal feedthrough - Sedighi, Behnam; Borokhovych, Yevgen; Gustat, Hans; Scheytt, Christoph (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper presents a new circuit for high-speed BiCMOS track-and-holds. The proposed approach improves the signal feedthrough in the hold mode and the bandwidth in the tracking mode. A prototype circuit is implemented in a 0.13 µm BiCMOS technology, operating at 10 GS/s and consuming 19 mW from 3.3 V supply. It is shown that the circuit is capable of providing a harmonic distortion below −50 dB.

Low-power 20-Gb/s SiGe BiCMOS driver with 2.5 V output swing - Sedighi, Behnam; Ostrovskyy, Philip; Scheytt, Christoph; Stille, Karl Stephan Christian; Böcker, Joachim (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper investigates low-power design of high-speed and high-swing electronic driver circuits. A method to estimate and optimize the power consumption of such driver ICs is presented. A 20-Gb/s driver circuit is fabricated in 0.25 µm SiGe BiCMOS process and an output swing of 2.5 V pp is measured. The driver consumes 0.75 W from 5 V supply.

Automated Source Code Annotation for Timing Analysis of Embedded Software - Joy, M. tech. Mabel Mary; Becker, Markus; Mathews, Emi; Müller, Wolfgang (In Proceedings of Advanced Computing and Communications Conference 2012 (ADCOM 2012))

Real-Time Android: Deterministic Ease of Use - Mauerer, Wolfgang; Hillier, Gernot; Sawallisch, Jan; Hönick, Stefan; Oberthür, Simon (Proceedings of Embedded Linux Conference Europe, 5. - 7. Nov. 2012)

Biologically Inspired Swarm Robotic Network Ensuring Coverage and Connectivity - Mathews, Emi; Graf, Tobias; Kulathunga, K. S. S. B. (In Proceedings of IEEE International Conference on Systems, Man, and Cybernetics (SMC 2012))

XEMU: An Efficient QEMU Based Binary Mutation Testing Framework for Embedded Software - Becker, Markus; Baldin, Daniel; Kuznik, Christoph; Joy, M. tech. Mabel Mary; Xie, Tao; Müller, Wolfgang (EMSOFT'12: Teenth ACM International Conference on Embedded Software 2012 Proceedings)

The System Verification Methodology for Advanced TLM Verification - Oliveira, Marcio F.; Kuznik, Christoph; Le, Hoang M.; Große, Daniel; Haedicke, Finn; Müller, Wolfgang; Drechsler, Rolf; Ecker, Wolfgang; Esen, Volkan (CODES/ISSS '12: Eighth IEEE/ACM/IFIP International Conference on Hardware/Software Codesign and System Synthesis Proceedings)

A Heuristic Energy-Aware Approach for Hard Real-Time Systems on Multi-Core Platforms - He, Da; Müller, Wolfgang (15th Euromicro Conference on Digital System Design (DSD))

Towards Hierarchical Self-Optimization in Autonomous Groups of Mobile Robots - Rasche, Christoph; Jungmann, Alexander; Schierbaum, Thomas; Werdehausen, Benjamin; Kleinjohann, Bernd (IEEE 10th International Conference on Industrial Informatics,)

Hierarchical Hybrid Planning for a Self-Optimizing Active Suspension System - Esau, Natascha; Krüger, Martin; Rasche, Christoph; Beringer, Steffen; Kleinjohann, Lisa; Kleinjohann, Bernd (7th IEEE Conference in Industrial Electronics and Applications)
This paper presents a hierarchical hyprid planning approach developed for realizing self-optimizing mechatronic systems. The hybrid planning approach is based on a discrete plan and a forecast of continuous system behavior generated by simulation during runtime. This does not only allow an online adaptation of a previously generated plan with regard to the actual system state as well as the current environmental conditions, even the planning objectives may be adapted to newly arising needs during system operation. The planner exploits the hierarchy already present in the system model by considering hierarchical parameterizations of the system as a discrete dimension of choice. The parameterizations are proposed by a novel hierarchical multiobjective optimization, which calculates Pareto points in a bottom up fashion, taking into account the constraints imposed by lower levels of the system hierarchy on the higher ones. Evaluations of the hierarchical hybrid planner in the context of an innovative railbound transport system show that it outperforms its non-hierarchical predecessor.

Evaluating Quality of Online Image Registration of Aerial Images Using Virtual Forces - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (Proceedings of The 16th International Conference on Image Processing, Computer Vision, & Pattern Recognition)

A First Step Towards Real-time Virtual Machine Migration in Heterogeneous Multi-Processor Systems - Grösbrink, Stefan (Symposium on System-integrated Intelligence)

Binary Mutation Testing Through Dynamic Translation - Becker, Markus; Kuznik, Christoph; Joy, M. tech. Mabel Mary; Xie, Tao; Müller, Wolfgang (42nd Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN))

Enhanced Schedulability Analysis of Hard Real-Time Systems on Power Manageable Multi-Core Platforms - He, Da; Müller, Wolfgang (Third International Symposium on Advances in Embedded Systems and Applications (ESA-2012))

Compilation of Methodologies to Speed up the Verification Process at System Level - Radke, Stephan; Rülke, Steffen; Oliveira, Marcio F.; Kuznik, Christoph; Müller, Wolfgang; Ecker, Wolfgang; Esen, Volkan; Hufnagel, Simon; Bannow, Nico; Oetjens, Jan-Hendrik; Brazdrum, Helmut; Janssen, Peter; et al. (edaWorkshop 12)

Process integrated wire-bond quality control by means of cytokine-Formal Immune Networks - Montealegre, Norma; Hagenkötter, Sebastian (Journal of Intelligent Manufacturing 23(3))

Towards Adaptive Resource Management for Virtualized Real-Time Systems - Grösbrink, Stefan; Oberthür, Simon; Baldin, Daniel (4th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2012))

Online Model Checking for Dependable Real-time Systems - Zhao, Yuhong; Rammig, Franz-Josef (16th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing-Shenzhen, China)

Agent-Based Modeling and Simulation of Artificial Immune Systems - Montealegre, Norma; Rammig, Franz-Josef (Third IEEE Workshop on Self-Organizing Real-Time Systems (SORT 2012))

Self-Coordination as Fundamental Concept for Cyber Physical Systems - Rammig, Franz-Josef (2nd SBC Workshop on Autonomic Distributed Systems - WoSiDA 2012)

Planarization of Geographic Cluster-based Overlay Graphs in Realistic Wireless Networks - Mathews, Emi (Ninth International Conference On Information Technology : New Generations (ITNG))

Online Energy-Efficient Hard Real-Time Scheduling for Component Oriented Systems - He, Da; Müller, Wolfgang (2012 IEEE 15th International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing (ISORC))

Efficient Alignment of Aerial Images Based on Virtual Forces - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (Proceedings of The Eighth International Conference on Autonomic and Autonomous Systems (ICAS))
Getting a contemporary aerial overview of a disaster area is a foremost task in search and rescue operations. We previously have introduced a novel method for registering a large amount of aerial images when camera parameters are almost unknown and no reference images are available. This paper provides two new methods, which improve our method for image registration based on virtual forces. The goal is to improve the performance of creating a contemporary overview map of a disaster area assembling several images taken by unmanned aerial vehicles (UAVs) equipped with cameras. In this paper, two new methods are introduced: a method for rotation estimation and a method for scale estimation. Both methods use fast heuristic approximation approaches and statistical methods to provide high robustness. We discuss the methods in detail and compare them to our previous approach regarding robustness and calculation speed. We can show that the new methods significantly increase the performance of the image registration process.

Efficient Color-Based Image Segmentation and Feature Classification for Image Processing in Embedded Systems - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa; Bieshaar, Maarten (Proceedings of the 4th International Conference on Resource Intensive Applications and Services (INTENSIVE))
In this paper, a color based feature extraction and classification approach for image processing in embedded systems in presented. The algorithms and data structures developed for this approach pay particular attention to reduce memory consumption and computation power of the entire image processing, since embedded systems usually impose strong restrictions regarding those resources. The feature extraction is realized in terms of an image segmentation algorithm. The criteria of homogeneity for merging pixels and regions is provided by the color classification mechanism, which incorporates appropriate methods for defining, representing and accessing subspaces in the working color space. By doing so, pixels and regions with color values that belong to the same color class can be merged. Furthermore, pixels with redundant color values that do not belong to any pre-defined color class can be completely discarded in order to minimize computational effort. Subsequently, the extracted regions are converted to a more convenient feature representation in terms of statistical moments up to and including second order. For evaluation, the whole image processing approach is applied to a mobile representative of embedded systems within the scope of a simple real-world scenario.

Dynamic Resource Management for Virtualized Mixed-Criticality Systems - Grösbrink, Stefan; Oberthür, Simon; Baldin, Daniel (Quo Vadis, Virtual Platforms? (in conjunction with Design, Automation and Test in Europe DATE 2012))

A SystemC Library for Advanced TLM Verification - Oliveira, Marcio F.; Kuznik, Christoph; Müller, Wolfgang; Ecker, Wolfgang; Esen, Volkan (Proceeding of Design and Verification Conference (DVCON))

A model-driven engineering framework for embedded systems design - Nascimento, Francisco A. M.; Oliveira, Marcio F.; Wagner, Flavio (Innovations in Systems and Software Engineering 8)

Balanced homodyne detection of optical quantum states at audio-band frequencies and below - Stefszky, Michael; Mow-Lowry, C M; Chua, S S Y; Shaddock, D A; Buchler, B C; Vahlbruch, H; Khalaidovski, A; Schnabel, R; Lam, P K; McClelland, D E (Classical and Quantum Gravity)

MOUSSE: scaling MOdelling and verification to complex heterogeneoUS embedded Systems Evolution - Becker, Markus; Gnokam Defo, Gilles Bertrand; Müller, Wolfgang; Fummi, F.; Pravadelli, G.; Vinco, Sara (Design, Automation and Test in Europe (DATE 2012))

Entscheidungsorientierte Planung unscharfer Erfolge von KMU in Supply Chains - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

XEMU: A QEMU Based Binary Mutation Testing Framework - Becker, Markus; Kuznik, Christoph; Joy, M. tech. Mabel; Xie, Tao; Müller, Wolfgang (Design, Automation and Test in Europe DATE)

Real-Time Android: Deterministic Ease of use - Mauerer, Wolfgang; Hillier, Gernot; Sawallisch, Jan; Hönick, Stefan; Oberthür, Simon (Proceedings of Embedded World Conference)

Image Segmentation For Object Detection on a Deeply Embedded Miniature Robot - Jungmann, Alexander; Schierbaum, Thomas; Kleinjohann, Bernd (Proceedings of the Seventh International Conference on Computer Vision Theory and Applications (VISAPP))
In this paper, an image segmentation approach for object detection on the miniature robot BeBot - a deeply embedded system - is presented. In order to enable the robot to detect and identify objects in its environment by means of its camera, an efficient image segmentation approach was developed. The fundamental algorithm bases on the region growing and region merging concept and identifies homogeneous regions consisting of adjacent pixels with similar color. By internally representing a contiguous block of pixels in terms of run-lengths, the computational effort of both the region growing and the region merging operation is minimized. Finally, for subsequent object detection processes, a region is efficiently translated into a statistically feature representation based on discretized moments.

Deterministic Runtime Adaptation for Hard Real-time Embedded Systems with Processing Constraints - Bin Tariq, Fahad (Proceedings of the 2nd International Conference on Pervasive Embedded Computing and Communication Systems)

Analyse des Bullwhip-Effekts in einer Supply Chain von KMU - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

A Localized Link Removal and Addition based Planarization Algorithm - Mathews, Emi; Frey, Hannes (13th International Conference On Distributed Computing And Networking (ICDCN))

Deployment of mobile routers ensuring coverage and connectivity - Mathews, Emi; Mathew, Ciby (International Journal of Computer Networks and Communications 4(1))

Virtual Prototyping of Cyber-Physical Systems - Müller, Wolfgang; Becker, Markus; Zabel, Henning; Elfeky, Ahmed; DiPasquale, Anthony (In Proceedings of 17th Asia and South Pacific Design Automation Conference (ASP-DAC 2012)

Swarm Robotic Time Synchronization for Object Tracking - Khaluf, Yara; Mathews, Emi; Rammig, Franz-Josef (Self-Organization in Embedded Real-Time Systems)

Biologically Inspired Information Technology: Towards a Cyber Biosphere - Rammig, Franz-Josef (Schemata und Praktiken)

Adaptive Web Services for Modular and Reusable Software Development - Bin Tariq, Fahad; Korrapati, Sandeep (Kapitel: F-DRARE: A Framework for Deterministic Runtime Adaptation of Cyber Physical Systems)

Wood-Plastic-Composites: Rheologische Charakterisierung und Füllverhalten im Spritzgießprozess - Kirchhoff, Nadine; Schröder, Cathrin; Stute, Daniel; Moritzer, Elmar; Schmid, Hans-Joachim (Chemie Ingenieur Technik)
Wood-Plastic-Composite (WPC) zeigen im Vergleich zu reinen Kunststoffen ein sehr unterschiedliches und überaus komplexes Material- und Fließverhalten. Letzteres ist für die Verarbeitung der Composite von entscheidender Bedeutung. Im Folgenden werden die Ergebnisse rheologischer Charakterisierungen sowie einiger Untersuchungen zum Füllverhalten im Spritzgießprozess dargestellt. Dabei werden auch auftretende Herausforderungen und mögliche Lösungsansätze diskutiert.

Sintering kinetics and mechanism of vitreous nanoparticles - Kirchhof, M.J.; Förster, H.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
The sintering of vitreous nanoparticle doublets is investigated numerically by a volume of fluid method coupled to Hamaker summation and experimentally by a high-temperature sintering flow reactor as well as by doublet shape analysis in the transmission electron microscope. In particular, the characteristic differences between nanoparticulate and bulk sintering are studied. The sintering mechanism of vitreous nanoparticles is determined to be viscous flow with interparticle van der Waals interactions acting as additional driving force. The early stages of the nanoparticle sintering kinetics are inversely proportional to the square of the particle size, instead of an indirect proportionality to the first order of the particle size for the entire bulk process. The transition between nanoparticulate and bulk sintering is localised to primary particle diameters of approx. 200–300 nm.

Towards an Integrated Service Rating and Ranking Methodology for Quality Based Service Selection in Automatic Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the Fourth International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
The paradigm shift from purchasing monolithic software solutions to a dynamic composition of individual solutions entails many new possibilities yet great challenges, too. In order to satisfy user requirements, complex services have to be automatically composed of elementary services. Multiple possibilities of composing a complex service inevitably emerge. The problem of selecting the most appropriate services has to be solved by comparing the different service candidates with respect to their quality in terms of inherent non-functional properties while simultaneously taking the user requirements into account.We are aiming for an integrated service rating and ranking methodology in order to support the automation of the underlying decision-making process. The main contribution of this paper is a first decomposition of the quality-based service selection process, while emphasizing major issues and challenges, which we are addressing in the On-The-Fly Computing project.

Towards the Application of Reinforcement Learning Techniques for Quality-Based Service Selection in Automated Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Services Computing (SCC))
A major goal of the On-The-Fly Computing project is the automated composition of individual services based on services that are available in dynamic markets. Dependent on the granularity of a market, different alternatives that satisfy the requested functional requirements may emerge. In order to select the best solution, services are usually selected with respect to their quality in terms of inherent non-functional properties. In this paper, we describe our idea of how to model this service selection process as a Markov Decision Process, which we in turn intend to solve by means of Reinforcement Learning techniques in order to control the underlying service composition process. In addition, some initial issues with respect to our approach are addressed.

Systematik zur Konzipierung von Produktionssystemen auf Basis der Prinziplösung mechatronischer Systeme - Nordsiek, Daniel

Systematik zur effizienten Bildung geospezifischer Umgebungsmodelle für Fahrsimulationen - Kreft, Sven

Vorausschau und Technologieplanung. 8. Symposium für Vorausschau und Technologieplanung

Master Election for Time Synchronization in Swarm Robotic Systems - Khaluf, Yara; Weiss, Fabian; Micus, Sebastian (The 10th IEEE International Symposium on Parallel and Distributed Processing with Applications)

Connectivity of Autonomous Agents Using Ad-hoc Mobile Router Networks - Mathews, Emi; Mathew, Ciby (Third International Conference on Networks & Communications, LNICST)

Quantification of nonclassicality - Gehrke, C.; Sperling, Jan; Vogel, W. (Physical Review A)

Strongly entangled light from planar microcavities - Pagel, D.; Fehske, H.; Sperling, Jan; Vogel, W. (Physical Review A)

Analytical progress on symmetric geometric discord: Measurement-based upper bounds - Miranowicz, Adam; Horodecki, Paweł; Chhajlany, Ravindra W.; Tuziemski, Jan; Sperling, Jan (Physical Review A)

Sub-Binomial Light - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review Letters)

Entanglement quasiprobabilities of squeezed light - Sperling, Jan; Vogel, W (New Journal of Physics)

True photocounting statistics of multiple on-off detectors - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Trading Venue Decision of Private Online Investors - Kundisch, Dennis (International Journal of Electronic Finance)